Noncentrosymmetric Cubic CsCdBO3 with Bichromophore. Issue 32 (2nd October 2013) - Yu, Hongwei; Wu, Hongping; Pan, Shilie; Zhang, Bingbing; Wen, Ming; Yang, Zhihua; Li, Hongyi; Jiang, Xiangzhan
Abstract: The noncentrosymmetric borate CsCdBO3 was synthesized by a solid‐state reaction, and its structure was determined by single‐crystal X‐ray diffraction. The crystal structure is a complicated three‐dimensional network composed of CdO6 octahedra, CsO6 octahedra, and BO3 triangles. Interestingly, CsCdBO3 crystallizes in the cubic space group P 21 3, which is quite rare for borate‐containing anisotropic polarized planar BO3 groups. Furthermore, the IR spectrum confirms the presence of BO3 groups. Second harmonic generation (SHG) measurements on powder samples reveal that the SHG response of CsCdBO3 is approximately 0.5 × KDP (KH2 PO4 ). Thermal analysis and UV/Vis/NIR diffuse reflectance spectroscopy data, as well as electronic band structure calculations, are also reported. Abstract : The noncentrosymmetric borate CsCdBO3 has been synthesized by a solid‐state reaction. It crystallizes in an interesting cubic system and has a second harmonic generation (SHG) response of approximately 0.5 × KDP (KH2 PO4 ).